Correlation of Anxiety Levels between Temporomandibular Disorder Patients and Normal Subjects. (14th September 2014) - Vasudeva, Subhash; Iyengar, Asha; Seetaramaiah, Nagesh
Abstract : Background. Temporomandibular disorders (TMDs) are among the common musculoskeletal conditions affecting the individual. Anxiety plays an important role in the pathogenesis of TMD. Modern lifestyle and work environment bring to focus the role of anxiety in everyday life which is changing the demographics of diseases like TMD. This study compared the anxiety scores between TMD patients and normal subjects. Material and Methods. 505 individuals were included in the study who were divided into group 1 with 255 individuals presenting with signs and symptoms of TMD and group 2 with 250 normal individuals as controls. Hospital anxiety depression scale was used to calculate the anxiety scores. Fischer's t test was used to compare the anxiety scores between the two groups. Results. 80% of individuals in group 2 and 44% in group 1 individuals had normal anxiety scores. 45% of the individuals in group 1 and 19% in group 2 had borderline anxiety scores. 11% of group 1 individuals and <1% of group 2 individuals demonstrated high anxiety scores. These results were statistically significant. Conclusion. Individuals with TMD exhibited higher levels of anxiety scores whereas significant number of control subjects exhibited normal anxiety scores.